Building transformational leaders: Assessing retail leadership maturity via an HR lens - Mariëtte Frazer; Lia M. Hewitt (SA Journal of Human Resource Management)
Orientation: The retail industry in South Africa is experiencing significant transformations due to Industry 4.0 and 5.0, necessitating a focused examination of leadership development maturity.